Rethinking Prophylaxis: Evaluating Surgical Site Infection Rates in Pediatric Orchidopexy without Prophylactic Antibiotics - Waqar Ullah, Naseem Khan, Amir Muhammad, Fazli Rashid, Khawar Saeed, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Undescended testes (UDT) is the most common congenital anomaly of the urogenital system in male newborns. Testicular descent into scrotum is necessary for normal spermatogenesis. The scrotal temperature is 2-7 degrees below body temperature. UDT are prone to impaired spermatogenesis, Surgical site infection (SSI) is a leading cause of postoperative morbidity and mortality. It is the third most common cause of hospital acquired infections. However injudicious use of antibiotics is responsible for increased costs, unwanted drug side effects like Clostridium difficile infection as well as the emergence of resistant strains and multidrug resistant infections. Objective: To determine the frequency of surgical site infection in pediatric patients undergoing orchidopexy without the administration of prophylactic antibiotics. Study Design: Descriptive Study Setting: Department of pediatrics, Lady Reading Hospital Peshawar. Duration of Study: From 08-July-2020 to 08-January-2021. Materials and Methods: In overall 126 respondents of undescended testis were selected in a consecutive manner OPD and subjected to orchidopexy. Follow up was done to detect the presence or absence or SSI. Results: The average age of the sample was 12.9+6.8 months. Mean weight of the included children was 12.8 4.9 kg and mean height was 73.1+ 13.5 cm. 50.8% Presented with right side undescended testis and 57.1% were in ASA class Mean operative time for orchidopexy was 44.4 10.3 minutes. SSI was recorded in 31 (24.6%) of children. Conclusion: Surgical site infection (SSI) is a significant concern in pediatric patients undergoing orchidopexy for unilateral undescended testis. Additional investigation is required to determine the factors that contribute to surgical site infections (SSI) in children and create successful measures for prevention. The use of prophylactic antibiotics should be carefully considered, considering the potential risks and benefits. Addressing SSI in this population is crucial for improving patient outcomes and reducing the burden of complications. Keywords: Orchidopexy, pediatrics, surgical site infection